A study of the adoption of innovation by Syrian farmers - Razzouk, Talal Ahmad (1990)
The objective of this research was to "investigate, study, analyse, and report conditions under which Syrian "rainfed" wheat farmers live interact and adopt innovations and improved cropping practices. The purpose of this was to help in understanding forces that can influence farmers' decisions to adopt innovations and which influence their adoption behaviour. The research, also, has attempted to develop concepts and methods which have rarely been used before in Syrian conditions.